Acardius mylacephalus: an infrequent diagnosis - Valia Hernández Viel; Alexander Llauger La Rosa; Margarita Argüelles Arza (Centro Provincial de Información de Ciencias Médicas, 2017)
The case report of a 21 years primigravida woman is presented to whom a monoamniotic and monochorial twin pregnancy was detected in the echographic exam at the Genetic Provincial Center of Santiago de Cuba.  The first fetus presented bilateral hydronephrosis predominantly in the left side, and the second rudimentary and deformed fetal structure, not well structured heart area and just arrhythmic and bradycardiac heart beats besides that the internal organs were not defined and everything was surrounded by severe cystic lymphangioma with big paravertebral cysts and a single umbilical cord with three vessels.  Everything described in the echogram was corroborated with the results of the autopsy, which corresponded with Acardius mylacephalus variety.